2011
DOI: 10.1007/s10653-011-9440-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of calcium in food, water and soil and its possible influence on rickets disease in Northern Nigeria

Abstract: Since the 1990s, children of the Gbagyi tribe in Northern Nigeria have been suffering severe rickets with an incidence of up to 40% in the children's generation. The disease seems to be prevalent in an area of approximately 100 km(2) south-east of Kaduna. According to broad medical studies in that area, there is no evidence for a genetic disposition but for a nutritional cause of the disease. A lack of calcium was found in blood and was calculated to originate from diet. We therefore checked parent material, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…These deficiencies might be caused by the low K concentrations in the pisolites, which serve as the parent materials of soil formation in these positions. In the pediment's soils, where granites containing K-bearing minerals, such as mica, formed the bedrock [16,26], K was found to be abundant. However, a link between K deficiency in soil and impaired bone mineralisation in children can generally be ruled out since K deficiency is not known to have any influence on bone structure [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These deficiencies might be caused by the low K concentrations in the pisolites, which serve as the parent materials of soil formation in these positions. In the pediment's soils, where granites containing K-bearing minerals, such as mica, formed the bedrock [16,26], K was found to be abundant. However, a link between K deficiency in soil and impaired bone mineralisation in children can generally be ruled out since K deficiency is not known to have any influence on bone structure [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research on F concentrations in drinking water from different CDR areas in developing countries showed that the F levels in the water were too low to could have had any impact on bone strength [14]. Instead, pilot studies in rural Kaduna area showed that total Ca concentrations were very low in soils and food crops [15,16], suggesting that a lack of Ca and other nutrients might be a predisposing factor to the CDR in the Kaduna area. Such relationship between nutrient deficiencies in soils and bone deformities in humans and animals is not new and has already been described from other areas [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Γαστρεντερικά έλκη προκαλούνται από αυξημένες συγκεντρώσεις ασβεστίου. Η μικρή ημερήσια πρόσληψη ασβεστίου (<50 mg/ημέρα) κατά το στάδιο της ανάπτυξης των μικρών παιδιών προκαλεί ανεπαρκή ανάπτυξη των οστών που συνοδεύεται από πόνο των οστών και εμφάνιση ραχίτιδας (Hartmann andSponholz 2011, Ross et. al.…”
Section: ηλεκτρική αγωγιμότητα (Ec)unclassified